Retaining humour in the translation subtitles of films : a study of Gnomeo & Juliet - Ang, Jennifer Poh Giok (Nanyang Technological University, 2020)
Despite many studies and theories developed, the translation of movies subtitles has generally not been taken as seriously as traditional literature or art forms. Possible reasons for this could be the short timeframe given for translation and the lack of understand of the movie’s background. Apart from a movie is an expressive visual medium where descriptive texts in the scripts have already been pre-translated into a visual medium during production and refined in post-production. It might be assumed that the audience can "see it for themselves". However, there have been many examples to demonstrate that the meaning or the intent of a movie can only be interpreted in totality with the combination of the visuals and the spoken lines. For the purpose of this dissertation paper, an English film title Gnomeo & Juliet, arguably for children, was chosen for analysis. Examining the Taiwanese Chinese translation, this study sought to identify common issues in translating adult content in films and possible strategies for resolving these issues. Results of the study revealed that with more thought put into maintaining the breviloquence, eloquence and relevance of the content, descriptive content suitable for adult understanding can still be educational and appealing to all ages. Hence, other than text level syntax and lexical semantics, subtitle translators are encouraged to place emphasis in the semiotics and logical semantics features of what both the source and target languages can offer.